Cerebral glucose metabolism in neurofibromatosis type 1 assessed with [18F]-2-fluoro-2-deoxy-D-glucose and PET. Issue 12 (December 1994) - Balestri, P; Lucignani, G; Fois, A; Magliani, L; Calistri, L; Grana, C; Di Bartolo, R M; Perani, D; Fazio, F
Abstract : Cerebral PET with [18F]-2-fluoro-2-deoxy-D-glucose has been performed in four patients with neurofibromatosis type 1 (NF1) to assess the relation between cerebral metabolic activity, MRI, and the presence of neurological symptoms, including seizures, as well as mental and language retardation. Widespread hypometabolism occurred in three of the patients. The lesions on MRI, which were localised in the subcortical white matter and grey structures, had normal rates of glucose metabolism. This finding suggests that the abnormalities seen on MRI are not due to defective blood supply, localised oedema, or grey matter heterotopic foci as previously hypothesised. The presence of the hypometabolic areas seems to be inconsistently related to the occurrence of seizures and is not proportional to the degree of mental impairment. This study provides evidence of a widespread cerebral hypometabolism that is not related to the presence of MRI abnormalities; conversely normal metabolism was present in the areas with an abnormal MRI signal.